2021
DOI: 10.1111/acps.13304
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders, psychopharmacological treatments, and mortality in 2150 COVID‐19 Spanish inpatients

Abstract: Objective To determine how mental disorders and psychopharmacological treatments before and during COVID‐19 hospital admissions are related to mortality. Methods Subjects included in the study were all adult patients with a diagnosis of COVID‐19, confirmed clinically and by PCR, who were admitted to a tertiary university hospital in Badalona (Spain) between March 1 and November 17, 2020. Data were extracted anonymously from computerized clinical records. Results 2,150 subjects were included, 57% males, mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 36 publications
6
49
1
1
Order By: Relevance
“…5,6 On the other hand, two large observational studies conducted in Europe (France and Spain), both demonstrated the significant, and positive association between antidepressant use and a reduced risk of intubation or death in patients admitted to hospital with COVID-19. 7,8 This data is strongly supported by the encouraging findings from clinical trials of the selective serotonin reuptake inhibitor (SSRI) fluvoxamine in the USA, in which treated patients exhibited a significantly lower likelihood of clinical deterioration, 9 or showed improved respiratory rates and significantly lower incidence of subsequent admission to hospital approximately 2 weeks after the onset of treatment. 10 It has also been postulated that some medications may alter the risk of COVID-19 infection following exposure by obstructing SARS-CoV-2 host cell entry, which occurs via the virus binding to the membrane-bound angiotensin-converting enzyme 2 (ACE2) in the nasal passages and lungs.…”
Section: Introductionmentioning
confidence: 91%
“…5,6 On the other hand, two large observational studies conducted in Europe (France and Spain), both demonstrated the significant, and positive association between antidepressant use and a reduced risk of intubation or death in patients admitted to hospital with COVID-19. 7,8 This data is strongly supported by the encouraging findings from clinical trials of the selective serotonin reuptake inhibitor (SSRI) fluvoxamine in the USA, in which treated patients exhibited a significantly lower likelihood of clinical deterioration, 9 or showed improved respiratory rates and significantly lower incidence of subsequent admission to hospital approximately 2 weeks after the onset of treatment. 10 It has also been postulated that some medications may alter the risk of COVID-19 infection following exposure by obstructing SARS-CoV-2 host cell entry, which occurs via the virus binding to the membrane-bound angiotensin-converting enzyme 2 (ACE2) in the nasal passages and lungs.…”
Section: Introductionmentioning
confidence: 91%
“…[13][14][15] In fact, an intake of functional inhibitors of acid sphingomyelinase activity medications, which inhibit the acid sphingomyelinase/ ceramide system and include fluoxetine hydrochloride and fluvoxamine maleate (among other medications), was associated with substantially reduced likelihood of intubation or death among hospitalized patients with COVID-19. 16,17 Although findings from some studies have suggested that psychiatric diagnosis, including mood and anxiety disorders, may be an independent risk factor for COVID-19 infection, 18,19 other epidemiological studies have suggested that major depression could be associated with reduced mortality in COVID-19, 20,21 possibly owing to the use of antidepressants in this population. 1,20 A recent observational study 1 showed a decreased mortality rate in hospitalized patients with COVID-19 who were prescribed antidepressants (n = 460), in particular SSRIs, but this study had limited power.…”
Section: Introductionmentioning
confidence: 99%
“…Clues regarding the mechanisms linking depression and poor outcomes in COVID-19 may be inferred from observational studies. For example, a recent study in a large Spanish sample of COVID-19 inpatients (n = 2150) found that a history of depression, but not the presence of de novo depressive symptoms, was associated with mortality [61]. This suggests that the pathways linking depression and increased mortality are not necessarily related to the current presence or severity of depressive symptoms, but to factors of a longer duration.…”
Section: Mechanisms Linking Depression and Obesity With Covid-19 Mortalitymentioning
confidence: 99%